(untitled) (Colombia Medica, 2019)
• Objective: To describe the presence of abuse in elderly people in Colombia and its association with socio-demographic and functional conditions. • Methods: Cross-sectional and descriptive research. Data were taken from the SABE Colombia Survey, a population study, with a national representative sample of 23,694 adults aged over 60 years. Presence and type of abuse by partners or family members, members were investigated. Generalized linear models with Poisson link function were used to estimate the causes of the prevalence of abuse by area of residence, region, age, sex, dependence on activities of daily living and living arrangements. • Results: 15.1% of the elderly in Colombia reported some type of abuse, and over 50% reported more than one form of abuse. Abuse proportion is greater in people who are aged 60-69, in women, people with lower levels of education, people who belong to lower socioeconomic status, people who live alone, people who live with children, and people in urban areas. The most frequent abuse form is psychological, followed by neglect and physical abuse. Dependence on basic and instrumental daily living activities increases the probabilities of suffering abuse. • Conclusions: Home is a risky place for the elderly people, especially for those with functional dependence, those who belong to low socioeconomic strata and women. Results should encourage debate among researchers, professionals and decision makers on public policy about necessary actions and means to change violent family dynamics in homes with elderly people.